Fórmula de Stiefel

La Fórmula de Stifel, dice: $$$\begin{pmatrix} m \\ n \end{pmatrix}+\begin{pmatrix} m \\ n+1 \end{pmatrix} =\begin{pmatrix} m+1 \\ n+1 \end{pmatrix}$$$

Veamos cómo se aplica:

$$\begin{pmatrix} 5 \\ 2 \end{pmatrix}+\begin{pmatrix} 5 \\ 3\end{pmatrix} = \begin{pmatrix} 6 \\ 3\end{pmatrix} $$

$$\begin{pmatrix} 2 \\ 1\end{pmatrix}+\begin{pmatrix} 2 \\ 2\end{pmatrix} = \begin{pmatrix} 3 \\ 2\end{pmatrix} $$

$$\begin{pmatrix} 90 \\ 89\end{pmatrix}+\begin{pmatrix} 90 \\ 88\end{pmatrix} = \begin{pmatrix} 91 \\ 89\end{pmatrix} $$

Ver problemas